Reconstruction of molecular networks involved in citokine-induced myotubes atrophy integrating microRNA and mRNA expression - Fernandez Garcia, Geysson Javier [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The skeletal muscle atrophy is a common phenomenon in many chronic systemic diseases such a sepsis, chronic heart failure, chronic obstructive pulmonary disease, chronic kidney disease, diabetes, AIDS and cancer. These diseases may be accompanied by a complex metabolic syndrome characterized by muscle wasting, denominated cachexia. The molecular pathways responsible for cachexia are not completely understood, however, evidence suggest that pro-inflammatory cytokines like Tumor Necrosis Factor (TNF)-α and Interferon (INF)-γ have a key role in molecular pathways related to loss of function and muscle mass. The complexity of mechanisms controlling gene expression in this process suggests the involvement of additional regulatory molecules, such as microRNAs; these RNA molecules encoded by the genome regulate the function of skeletal muscle during development and various muscle diseases. MicroRNAs orchestrate common pathways or biological function, this unique feature gives rise as an effective tool for determining the pathways involved in specific diseases or biological processes. The hypothesis of this work is that the muscle atrophy induced by TNF-α and INF-γ has a microRNAs expression profile that allow the identification of regulatory networks and molecular pathways
Keywords: Atrofia muscular; Sistema musculoesquelético; Síndrome metabólica; Caquexia; Metabolic syndrome